Barriers to the Adoption of Climate-Smart Dry Direct-Seeded Rice Systems in Bangladesh - Ahmed, Sharif; Bhandari, Humnath; Kumar, Virender (International Rice Research Institute, 2025)
This technical report focuses on barriers to adopting climate-smart dry direct-seeded rice (DSR) systems in Bangladesh, where traditional transplanted rice cultivation is resource-intensive and contributes to higher greenhouse gas emissions. Although DSR offers advantages like reduced water and labor requirements and fewer emissions, its adoption in Bangladesh remains limited at around 8%. The suitability of DSR varies across Bangladesh's diverse agro-ecological zones. Drought-prone northwestern regions can leverage DSR to reduce water usage and accelerate crop establishment. Eastern hilly areas benefit from DSR's adaptability due to its lower tillage requirements, especially for aus and aman rice. However, flood-prone northeastern haor regions are unsuitable for DSR, while southwestern coastal zones face salinity and water scarcity in the dry season and flood challenges in the wet season, though aus DSR shows promise. Recent initiatives by IRRI in collaboration with BRRI and DAE from 2022 to 2025 have actively promoted DSR through trials, demonstrations, and training programs. These efforts include testing rice varieties suitable for late boro conditions with DSR systems, evaluating establishment methods and varieties in the aman season, capacity development for farmers, and training local service providers (LSPs) to operate mechanized seeders. A notable achievement in 2025 was the successful establishment of 200 acres of mechanized aman DSR in the Nilphamari district. Dissemination of DSR knowledge has been further amplified through the distribution of production technology booklets, publications in agricultural magazines (Krishikotha, published by AIS), and the results demonstration program (FFD). These activities have raised awareness and encouraged farmers to adopt DSR for higher productivity and sustainability.